Mechanisms of Stress Tolerance in Cyanobacteria under Extreme Conditions - Priya Yadav; Rahul Prasad Singh; Shashank Rana; Diksha Joshi; Dharmendra Kumar; Nikunj Bhardwaj; Rajan Kumar Gupta; Ajay Kumar (Stresses, 2022)
Cyanobacteria are oxygen-evolving photoautotrophs with worldwide distribution in every possible habitat, and they account for half of the global primary productivity. Because of their ability to thrive in a hostile environment, cyanobacteria are categorized as “extremophiles”. They have evolved a fascinating repository of distinct secondary metabolites and biomolecules to promote their development and survival in various habitats, including severe conditions. However, developing new proteins/enzymes and metabolites is mostly directed by an appropriate gene regulation system that results in stress adaptations. However, only few proteins have been characterized to date that have the potential to improve resistance against abiotic stresses. As a result, studying environmental stress responses to post-genomic analysis, such as proteome changes using latest structural proteomics and synthetic biology techniques, is critical. In this regard, scientists working on these topics will benefit greatly from the stress of proteomics research. Progress in these disciplines will aid in understanding cyanobacteria’s physiology, biochemical, and metabolic systems. This review summarizes the most recent key findings of cyanobacterial proteome study under various abiotic stresses and the application of secondary metabolites formed during different abiotic conditions.